PERAN MAHASISWA DALAM MITIGASI COVID-19 MELALUI PROGRAM KULIAH KERJA NYATA SECARA DARING DAN LURING - Valentin, A.P.; Sukarsa, I.K.G. (Buletin Udayana Mengabdi; Vol 20 No 1 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i01.p10, 2021)
The Udayana University Community Service Program was carried out differently from the previous year. The Covid-19 pandemic has made KKN students appointed as agents of health protocol for the community. For this reason, students from Banyuwangi form the Udayana University Community Service Community Service Volunteer Team. The Udayana University Community Service Community Service Volunteer Team had the opportunity to carry out activities in Sukonatar Village, Srono District, Kab. Banyuwangi with the theme "Sukonatar Village Responds to Covid-19 Mitigation". This time the KKN was carried out online and in combination, for one month and one week the students compiled a schedule tailored to each work program in three fields, namely Public Health and Kesling, Education, and Social and Economy. Based on the grouping of the three areas that have been mentioned, it is intended to overcome the problems that arise by providing solutions with solution ideas, so that the community can survive even during a pandemic. In addition, it is also hoped that with a form of contribution of thoughts and energy from students regarding the prevention and handling of Covid-19 it can help the community a little, especially in Sukonatar Village.